Running educational outreach meetings in general practice. Issue 12 (18th December 2017) - Petty, Duncan; Wood, Su; Glidewell, Liz
Abstract : Educational outreach meetings are an evidence‐based way of making long‐term behaviour changes, such as improving prescribing. This article discusses how to run educational outreach meetings to obtain the best possible outcomes in general practice.